PERAN BRAND LOVE MEMEDIASI PENGARUH BRAND TRUST TERHADAP BRAND LOYALTY PADA KONSUMEN KOBER MIE SETAN - Dirayani, Ade Mela Dewi; Mandala, Kastawan (E-Jurnal Manajemen, 2022)
Brand loyalty is the attachment that customers have to a brand, motivating customers to show consistent buying behavior from the preferred brand. The high brand loyalty can be influenced by several factors including brand trust and brand love. The purpose of this study is to determine the role of brand love in mediating the effect of brand trust on brand loyalty on consumers of Kober Mie Setan in Denpasar with 120 respondents, with a non-probability sampling technique of determining the sample with the purposive sampling method. Data was collected through google form questionnaire. The analysis technique used is Path Analysis. The results indicate that brand trust has a positive and significant effect on brand loyalty. Brand trust has a positive and significant effect on brand love. Brand love has a positive and significant effect on brand loyalty. Brand love partially mediates the effect of brand trust on brand loyalty. Keywords:, brand loyalty, brand trust, brand love